Is environmental health really a part of economic development - or only an afterthought? - Listorti, James A. (1998)
This paper highlights the lack of consideration given to health and the absence of health professionals in decision-making processes in most development projects. This is illustrated by an analysis of World Bank infrastructure projects. Yet, as the paper explains, improved infrastructure may be able to relieve up to 44 per cent of the disease burden in low and middle-income countries and do so at a fraction of the cost of investments in health care. Thus, it might be possible to extract as many (or more) health improvements for a lower cost through investments outside the health sector. The paper also gives examples of the economic benefits that arise from the inclusion of health factors in policy and these can help justify investments that could otherwise be considered too costly. - Reproduced
Keywords: Economic and social development; Environmental health